Setting a Good Example? Examining Sibling Spillovers in Educational Achievement Using a Regression Discontinuity Design - Krzysztof Karbownik; Umut Özek (Institute of Labor Economics (IZA), 2021)
Using a regression discontinuity design generated by school-entry cutoffs and school records from an anonymous district in Florida, we identify externalities in human capital production function arising from sibling spillovers. We find positive spillover effects from an older to a younger child in less affluent families and negative spillover effects from a younger to an older child in more affluent families. These results provide empirical evidence that educational policies could create both positive and negative within-family externalities depending on the characteristics of the affected households.
Keywords: D13; I20; J13; 330; school starting age; sibling spillovers; human capital externalities